The Importance Of Voluntary Cooperation Between Citizens And The Police - مكائيل تميم (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The police institution has many and many functions in society, and it is defined according to legal and administrative laws and regulations. One of the most important basic job duties of the police is to prevent, combat, detect and arrest the perpetrators, implement the punishment imposed on them, protect the citizen and his property and protect public money, And achieving security and stability for the members of the community, and for this security establishment to perform its professional duties it must be acceptable to the community in order to obtain assistance, because it may not be acceptable and it is implementing laws that conflict with some of the whims and desires of members of the community.The police alone find themselves unable to fulfill all of their duties with a high degree of efficiency without the participation of citizens with them, but some citizens have some reservations towards the police, so we may find a kind of reluctance to cooperate as a result, and sometimes it may even reach the police’s obstruction .The citizen’s need for security requires him to cooperate with the police, therefore the police must take the initiative to create a positive reciprocal relationship with the citizen as the picture will change if this security institution introduces some reforms to the traditional arena in which it performs its duties, because in the event that the citizen does not cooperate with the police leads to Negative effects on the security situation in the community, therefore it is necessary to achieve effective cooperation between the police and the community to achieve security and stability for the members of the community.